A novel hybrid III–V/silicon deformed micro-disk single-mode laser. (1st February 2015) - Feng, Peng; Zhang, Yejin; Wang, Yufei; Liu, Lei; Zhang, Siriguleng; Wang, Hailing; Zheng, Wanhua
Abstract A novel hybrid III–V/silicon deformed micro-disk single-mode laser connecting to a Si output waveguide is designed, and fabricated through BCB bonding technology and standard i-line photolithography. Compared to a traditional circular micro-disk in multi-longitudinal-mode operation, unidirectional emission and single longitudinal-mode output from a Si waveguide are realized. In the experiments, an output power of 0.31 mW and a side-mode suppression ratio of 27 dB in the continuous-wave regime are obtained.